Upregulated HMGB1 levels in maternal–fetal interface of patients with unexplained recurrent spontaneous abortion from different sources. (12th December 2022) - Wang, Jing; Zhu, Damin; Yin, Jiaqian; Ma, Cong; Peng, Xiaoqing; Zou, Huijuan; Cao, Yunxia; Xu, Xiaofeng
Abstract: Objective: To investigate the expression and sources of high mobility group box 1 (HMGB1) protein in the maternal–fetal interface of patients with unexplained recurrent spontaneous abortion (URSA), and further to verify the role of HMGB1 in the etiology of URSA. Methods: 55 women at early pregnancy with URSA and 55 women undergoing selective termination of normal early pregnancy as control were included. The abortion tissues including villi and decidua were collected. The expression of HMGB1, CD45, CK7, and vimentin in abortion tissues was detected, and the localization and sources of HMGB1 were analyzed. Results: Infiltrating immune cells and expression of HMGB1 were significantly increased in villi and decidua in URSA group compared with those in the control group. In the URSA group, HMGB1 was colocalized with the CD45-labeled immune cells, and it was more obvious in decidua than in villi; in addition, HMGB1 was colocalized with the vimentin-labeled decidual stromal cells, but not with the CK7- labeled villous epithelial cells. Conclusion: High expression of HMGB1 in the maternal–fetal interface in URSA patients was actively secreted by the infiltrating immune cells, and decidual stromal cells may passively release HMGB1 during necrosis.